Geographical and climatic contributions to melioidosis hotspot formation in Southern Taiwan - Chen, Kuang-Yueh; Chen, Kuang-Ying; Ho, Hsin-Ping; Lin, Hsi-Hsun; Hsu, Bing-Mu; Chen, Yao-Shen; Hsu, Duen-Wei; Ren, Chung-Yuan (PLoS neglected tropical diseases, 2025)
Melioidosis outbreaks in Taiwan frequently coincided with severe typhoons. Over a 20-year period, 782 cases of melioidosis were reported, with outbreaks often clustering in a specific hotspot area. We hypothesized that the unique hilly terrain in this hotspot trapped contaminated aerosols generated from northern to northwestern farming land within the area and restricted their spread beyond it. Across Taiwan, and particularly within the hotspot, weekly melioidosis incidence was significantly correlated with heavy rainfall and strong wind speed with time lags of 0, 1 and 2 weeks. When rainfall exceeded 200 mm and wind gust speeds reached over 20 m/sec, melioidosis outbreaks were frequently observed. Additionally, melioidosis incidence was associated with riverbank repair activities, indicating severe flooding caused by typhoons. Environmental confounding factors, such as CH₄, CO, NO, NO₂, NO x , O₃, particulate matter (PM) 10 , PM 2.5 , SO₂, and total hydrocarbon (THC), fluctuated seasonally but were not correlated with melioidosis cases. Aerosol sampling revealed that concentrations of contaminated aerosols were markedly higher north of the hill, where farming land was more prevalent, compared to the south, which had no farming land and was primarily residential. In addition to heavy rainfall and strong wind speed, shifts in wind direction from southwesterly to northwesterly during typhoons appeared to concentrate aerosols in the northern area but not in the south. Higher seropositive rates for Burkholderia pseudomallei antibodies in northern residents, compared to those in the south, further suggested increased exposure to pathogen-laden aerosols in the northern hotspot. This study demonstrated that heavy rainfall, combined with strong directional winds, generated high concentrations of contaminated aerosols from farming land in specific hilly terrains, leading to localized melioidosis outbreaks. It provided a valuable example of geographical, and climatic factors driving the formation of melioidosis hotspots in subtropical regions such as southern Taiwan.